Windows 98 : the complete reference - Levine, John; Young, Margaret Levine; Muder, Doug; Barrows, Alison (New Delhi : Tata McGraw-Hill, 1998)
Computer science
Keywords: Windows; Computer programming; Hardware; Graphics; Internet; E-mail; World wide web